2007
DOI: 10.1287/msom.1060.0131
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Influence of Operational Intellectual Capital on Capabilities and Performance

Abstract: Managers have long been challenged by an abundance of internal and external demands and uncertainties in their operating environments. Anecdotal evidence and a growing number of research studies have advocated process flexibility and product innovation as organization-level operating capabilities critical for responding to such demands and uncertainties, and have highlighted the need for more efficient and effective management of the firm's knowledge-based resources. Leveraging arguments from the resource-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
168
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(172 citation statements)
references
References 131 publications
2
168
1
1
Order By: Relevance
“…Particularly, Rappaport (1987) points out that business performance takes into account the responsibilities and profit maximisation objectives of an organisation, while environmental performance indicates to the environmental responsibilities of an organisation . Additionally, based on previous studies, business performance can be conceptualised with the two aspects of market and financial performance (Menor et al, 2007;Yang et al, 2011;Narasimhan and Kim, 2002). …”
Section: Green and Lean Practice And Organisational Performancementioning
confidence: 99%
“…Particularly, Rappaport (1987) points out that business performance takes into account the responsibilities and profit maximisation objectives of an organisation, while environmental performance indicates to the environmental responsibilities of an organisation . Additionally, based on previous studies, business performance can be conceptualised with the two aspects of market and financial performance (Menor et al, 2007;Yang et al, 2011;Narasimhan and Kim, 2002). …”
Section: Green and Lean Practice And Organisational Performancementioning
confidence: 99%
“…While there has been quite a lot of research on the nature and the components of knowledge and intellectual capital, or IC (e.g., Edvinsson & Malone, 1997;Sveiby, 1997), and some research has shown that an important level of knowledge or IC is apparently correlated with a good performance and innovation (Hsu & Sabherwal, 2011;Menor et al, 2007), it remains unclear how this intellectual capital or knowledge can be gained and to what extent collective institutions can contribute to this in all sectors of activity.…”
Section: Resultsmentioning
confidence: 99%
“…Also, knowledge and intellectual capital have replaced physical capital as the main source of competitiveness and creation of a competitive advantage over other firms (Drucker , 1993(Drucker , , 1988. While there has been quite a lot of research on the nature and the components of knowledge and intellectual capital, or IC (e.g., Edvinsson & Malone, 1997;Sveiby, 1997), and some research has highlighted the fact that an important level of knowledge or IC is apparently correlated with a good performance (Hsu & Sabherwal, 2011;Menor et al, 2007), it is often unclear how this intellectual capital or knowledge can be gained but the collective leadership and exchanges are put forward, contributing to reduce the validity or importance of the orthodox view, ie. the neoclassical individualistic view.…”
Section: Innovation In the It Sector : Intermediary Organizations As mentioning
confidence: 99%
“…This is the case of the studies published by Brookes et al (2007) and Menor et al (2007) which aim at explaining product innovation performance by means of social capital and knowledge-based resources, respectively. However, Wu et al (2007) represent an exception to this trend, as they adopt a holistic IC perspective in order to explain technological innovation performance.…”
Section: Intellectual Capital Categoriesmentioning
confidence: 99%